Microplastic pollution in marine environment - Zon, Nur Farhan; Azman, Shamila; Supian, Nur Sumaiyyah (Penerbit UTM Press, 2020)
Plastic is constructed from linking of hydrocarbon monomers and produced synthetic polymers. Plastic production reported is growing up steadily each year due to its demand based on Figure 2.1. Current production reported to be up to 348 million tonnes in 2017 (Plastic Europe, 2018).